A randomized controlled trial of adjuvant mitomycin‐c in endoscopic surgery for laryngotracheal stenosis. (25th April 2019) - Yung, Katherine C.; Chang, Joseph; Courey, Mark S.
Abstract : Objectives/Hypothesis: Topical mitomycin‐C (MMC) application is a commonly accepted adjuvant therapy in the surgical treatment for laryngotracheal stenosis (LTS). However, the efficacy of MMC has not been examined in a prospective, randomized clinical trial in humans. We aimed to examine the efficacy of MMC in the treatment of LTS patients as compared to a placebo‐controlled group. Study Design: Prospective, randomized, double‐blind, placebo‐controlled clinical trial. Methods: Fifteen patients with LTS were enrolled in a 24‐month trial and randomized into one of two groups: 1) endoscopic surgical treatment with topical application of MMC or 2) endoscopic surgical treatment with topical application of saline. Postoperatively, patients were evaluated at standardized intervals with a symptom questionnaire and spirometry. Subsequent surgery was performed as needed based on relapse of stenosis on exam and patient‐reported symptom severity. Results: The average interval between surgical treatments was 17.9 months in the placebo group and 17.4 months in the MMC group ( P = .95). There was no difference in magnitude of peak inspiratory flow (PIF) improvement between groups. The average magnitude of PIF change was 1.3 L/sec and 1.1 L/sec for the placebo and MMC groups, respectively ( P = .64). Similarly, there was no difference in magnitude of symptom improvement or duration of symptom improvement between the two groups. Conclusions: This prospective, randomized. double‐blind. placebo‐controlled trial suggests that the use of MMC as a topical adjuvant therapy has no additional benefit in the endoscopic surgical management of LTS. Further study is needed. Level of Evidence: 1b Laryngoscope, 130:706–711, 2020